Differences in motor abilities between female basketball and volleyball players - Cacic, I.; Rupcic, T.; Dukaric, V.; Feng, L.; Cigrovski, V. (Croatian Sports Medicine Journal, 2020)
The research took place at the Faculty of Kinesiology in Zagreb. The goal of the research was to determine differences in motor skills, between the youth categories, of the female volleyball and basketball players. Sample size was comprised of 35 female athletes with an average age of 14,7 ± 0,8 years, average body height 176,9 ± 8,1 cm, and average body weight 65,4 ± 6,8 kg. Descriptive statistic was used to analyse the results, which had showed descriptive method indicators (Min, Max, Mean, Sd). The tests that were conducted for analysis in the research were: side steps (MAGKUS), countermovement jump (CMJ), single leg take-off from a step (Single_leg), two-legged take-off with one step approach (Parallel_jump) and 20 m running (Run_20m). For the purpose of determining the statistical significance of differences between groups of subjects, the independent samples t-test was used in the software package Statistica v13.5. A statistically significant difference was found in countermovement jump, two-legged take-off with one step approach and side steps, in which the group of volleyball players had significantly better results. Remaining variables did not show any significant results. This research will contribute to a better understanding of the similarities and differences between basketball and volleyball. With the presented tests and results, it is possible to continuously monitor athletes and use these values as reference points for comparing equal categories of female athletes.